INVESTIGASI EMPIRIS DETERMINAN KEPATUHAN WAJIB PAJAK ORANG PRIBADI: TINJAUAN KOMPREHENSIF PADA ASPEK KESADARAN, EFEKTIVITAS SANKSI, DAN KUALITAS PELAYANAN FISKUS - Yeni Tata Rini; Rizal Martandi Lubis; Rony Hendra Hertanto (Publika Citra Media, 2026)
This study aims to elucidate the determinants of Individual Taxpayer (WPOP) compliance, specifically targeting the freelance professional segment within the jurisdiction of KPP Pratama Malang Utara. It addresses inconsistencies in prior empirical findings (research gap) by re-examining the influence of taxpayer awareness, tax sanctions, and fiscal service quality on compliance levels. Adopting a quantitative design with an associative approach, this research utilized a proportional random sampling technique to obtain a representative respondent pool. Hypothesis testing was conducted via multiple linear regression analysis using statistical software to validate causal relationships between variables, both partially and simultaneously. Empirical investigations confirm that taxpayer awareness, tax sanctions, and fiscal service quality simultaneously and partially contribute significantly and positively to taxpayer compliance. The regression model explains 66.6% of the compliance variability, indicating that the combination of cognitive understanding (internal factors) with regulatory instruments and service quality (external factors) serves as a robust predictor for driving fiscal discipline. This study enriches taxation literature by validating compliance theories that integrate psychological aspects with the deterrence effect. The findings bridge previous academic debates by demonstrating that, within a high-density economic demographic, sanctions and service quality remain highly relevant determinants. The study is limited to three independent variables, leaving 33.4% of the variability unexplained, and is bound by a specific geographical focus. This opens avenues for future research to explore other moderating variables or expand the regional scope. The findings suggest that tax authorities should not rely solely on rigid law enforcement but must also intensify persuasive strategies through partnerships with the business sector and the enhancement of integrated, data-driven service quality. The study's originality lies in its specific focus on the